Electrode for lithium ion secondary battery, method for manufacturing same, and lithium ion secondary battery including same
By forming a porous layer containing polymer binder and inorganic fine particles on the electrode of the lithium-ion secondary battery, the problem of short circuit between the positive electrode and the negative electrode at high temperature is solved, and the stability and life of the battery are achieved.
Patent Information
- Application Number
- CN202480002345.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2024-04-01
- Publication Date
- 2024-12-24
AI Technical Summary
Lithium-ion secondary batteries cause extreme heat shrinkage due to the short circuit between the positive electrode and the negative electrode at high temperatures, affecting the stability and life of the battery.
Using a porous layer containing a polymer binder and inorganic fine particles, the flexibility and adhesion of the porous layer is improved by forming a tightly bonded porous layer on the electrode active material layer, and copolymers of hard and soft segments are used to improve the flexibility and adhesion of the porous layer. Prevent short circuits.
The lithium-ion secondary battery maintains stability and extends the battery life at high temperatures. By combining the closely-bonded porous layer and the electrode active material layer, the durability and performance of the battery are improved.
Smart Images

Figure CN119183615A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0053337 filed in the Korean Intellectual Property Office on April 24, 2023, and Korean Patent Application No. 10-2024-0042820 filed in the Korean Intellectual Property Office on March 28, 2024, the disclosures of which are incorporated herein by reference in their entirety.
[0003] The present disclosure relates to an electrode for a lithium ion secondary battery, a method of manufacturing the same, and a lithium ion secondary battery including the same. Background Art
[0004] Recently, with the development of technology and the increase in demand for mobile devices, the demand for charging / discharging secondary batteries as energy sources has increased rapidly, and therefore various studies on secondary batteries that can meet various needs have been conducted. In addition, secondary batteries have attracted considerable attention as power sources for electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (HEV), etc., which have been developed to solve air pollution caused by existing gasoline and diesel vehicles using fossil fuels.
[0005] When a lithium ion secondary battery causes a short circuit due to contact between the positive electrode and the negative electrode, this results in the generation of great heat and explosion. Therefore, a porous separator is applied to a lithium arc battery, but due to the characteristics of its material and its manufacturing process including stretching, the porous separator of the secondary battery shows extreme thermal shrinkage behavior at a temperature of about 100°C or higher, which causes a problem of causing a short circuit between the positive electrode and the negative electrode.
[0006] Therefore, there is a need to study a lithium ion secondary battery that includes a separator having excellent coating characteristics and can achieve stability and long battery life characteristics at high temperatures. Summary of the invention
[0007] Technical issues
[0008] An object of the present disclosure is to provide an electrode for a lithium ion secondary battery having excellent bonding durability between a porous layer and an electrode substrate.
[0009] Another object of the present disclosure is to provide a method of manufacturing an electrode for a lithium ion secondary battery.
[0010] Still another object of the present disclosure is to provide a lithium ion secondary battery including the electrode.
[0011] Technical Solution
[0012] According to one embodiment of the present disclosure, there is provided an electrode for a lithium ion secondary battery, comprising:
[0013] The electrode active material layer and the porous layer are laminated on the electrode current collector layer,
[0014] The porous layer comprises a polymer binder and inorganic fine particles dispersed in the polymer binder, wherein the polymer binder comprises a copolymer comprising a hard segment of the following Chemical Formula 1 and a soft segment of the following Chemical Formula 2:
[0015] [Chemical formula 1]
[0016]
[0017] Wherein in Chemical Formula 1,
[0018] R 1 and R 3 Each independently Among them A 1 To A 3 are each independently hydrogen or an alkyl group having 1 to 3 carbon atoms, and L 1 is a chemical bond or a methylene group;
[0019] R 2 is an alkylene group having 1 to 5 carbon atoms;
[0020] [Chemical formula 2]
[0021]
[0022] Wherein in Chemical Formula 2,
[0023] R 4 It is an alkylene group having 3 to 6 carbon atoms.
[0024] According to another embodiment of the present disclosure, there is provided a method for manufacturing an electrode for a lithium ion secondary battery, the method comprising the following steps:
[0025] forming an electrode active material layer by applying an electrode material composition including an electrode active material to an electrode current collector layer;
[0026] preparing an inorganic fine particle dispersion in which inorganic fine particles and a dispersant are dispersed in a solvent;
[0027] preparing a binder solution comprising a polymer binder comprising a copolymer including a hard segment of Chemical Formula 1 and a soft segment of Chemical Formula 2 dissolved in a solvent;
[0028] preparing a slurry for forming a porous layer by mixing a binder solution with an inorganic fine particle dispersion; and
[0029] The porous layer is formed by applying a slurry for forming a porous layer onto the electrode active material layer.
[0030] According to another embodiment of the present disclosure, there is provided a slurry for forming a porous layer of an electrode for a lithium ion secondary battery, including: a polymer binder and inorganic fine particles dispersed in the polymer binder.
[0031] According to still another embodiment of the present disclosure, provided is a lithium ion secondary battery including the electrode for a lithium ion secondary battery.
[0032] Now, an electrode for a lithium ion secondary battery, a method of manufacturing the same, and a lithium ion secondary battery including the same according to an embodiment of the present disclosure will be described in more detail.
[0033] The terms or words used in this specification and claims should not be construed as limited to common terms or dictionary terms, but the present invention should be interpreted with meanings and concepts consistent with the technical ideas of the present disclosure based on the principle that the inventor can appropriately define the concepts of the terms to appropriately describe his own invention in the best manner.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention belongs. The terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the scope of the invention.
[0035] As used herein, the singular forms “a,” “an,” and “the” are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0036] It should be understood that the terms "comprising", "including", "having" and the like are used herein to specify the presence of stated features, regions, integers, steps, actions, elements and / or components, but do not exclude the presence or addition of other features, regions, integers, steps, actions, elements, components and / or groups.
[0037] Although the present invention can be modified in various ways and adopt various alternative forms, its specific embodiments are described and described in detail below. However, it should be understood that it is not intended to limit the present invention to the specific forms disclosed, but on the contrary, the present invention covers all modifications, equivalents and alternatives that fall within the spirit and scope of the present invention.
[0038] When describing a positional relationship, for example, when the positional relationship is described as "on," "above," "below," and "immediately adjacent to," one or more other parts may be arranged between the two parts, unless "just" or "directly" is used.
[0039] When describing a time relationship, for example, when a time sequence is described as "after," "subsequently," "next," and "before," discontinuous cases may be included unless "just" or "directly" is used.
[0040] As used herein, the term “at least one” should be understood to include any and all combinations of one or more of the associated listed items.
[0041] In the present invention, any one layer being bonded to another layer "through" another layer means that one layer and another layer are stacked and bonded through the another layer in at least a partial region interposed between the one layer and another layer.
[0042] According to one embodiment of the present disclosure, there is provided an electrode for a lithium ion secondary battery, comprising:
[0043] The electrode active material layer and the porous layer are stacked on the electrode current collector layer,
[0044] The porous layer comprises a polymer binder and inorganic fine particles dispersed in the polymer binder, wherein the polymer binder comprises a copolymer comprising a hard segment of the following Chemical Formula 1 and a soft segment of the following Chemical Formula 2:
[0045] [Chemical formula 1]
[0046]
[0047] Wherein in Chemical Formula 1,
[0048] R 1 and R 3 Each independently Among them A 1 To A 3 are each independently hydrogen or an alkyl group having 1 to 3 carbon atoms, and L 1 is a chemical bond or a methylene group;
[0049] R 2 is an alkylene group having 1 to 5 carbon atoms;
[0050] [Chemical formula 2]
[0051]
[0052] Wherein in Chemical Formula 2,
[0053] R 4 It is an alkylene group having 3 to 6 carbon atoms.
[0054] As a result of further studies by the present inventors, it was determined that an electrode for a lithium ion secondary battery satisfying the above configuration has close bonding between the porous layer and the electrode active material layer and also imparts high flexibility to the porous layer, thereby being able to exhibit excellent durability during charge and discharge.
[0055] According to one embodiment of the present disclosure, the electrode for a lithium ion secondary battery may be a negative electrode or a positive electrode.
[0056] Electrode current collectors known in the art to which the present disclosure belongs that have conductivity and do not cause any chemical changes in lithium ion secondary batteries can be applied to the electrode current collector layer. In one example, the electrode current collectors that can be used include stainless steel; aluminum; nickel; titanium; fired carbon; or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc.
[0057] Preferably, the thickness of the electrode current collector may be 3 μm to 500 μm. The electrode current collector may form fine protrusions and depressions on its surface to enhance adhesion to the electrode material. The electrode current collector may be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabric structures.
[0058] The electrode active material layer includes an electrode material composition, which is a mixture of an electrode active material, a conductive material, and a binder.
[0059] Conductive materials can be used to impart electronic conductivity to the electrodes.
[0060] The conductive material can be used without particular limitation, as long as it has electronic conductivity without causing any chemical changes in the lithium ion secondary battery. As a non-limiting example, the conductive material may include carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; graphite such as natural graphite and artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives. As the conductive material, any single one of the above examples or a mixture of two or more thereof may be used.
[0061] The content of the conductive material can be adjusted within a range that does not cause a decrease in the capacity of the battery while exhibiting an appropriate level of conductivity. Preferably, the content of the conductive material can be 1 wt % to 10 wt %, or 1 wt % to 5 wt %, based on the total weight of the electrode material.
[0062] The binder is used to properly adhere the electrode material composition to the electrode current collector.
[0063] As non-limiting examples, the binder may include polyvinyl alcohol, polyacrylate, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon resin, etc. As the binder, one of the above examples or a mixture of two or more thereof may be used.
[0064] The content of the binder can be adjusted within a range that does not cause a decrease in the capacity of the battery while exhibiting an appropriate level of binding properties. Preferably, the content of the binder can be 1 wt % to 10 wt %, or 1 wt % to 5 wt %, based on the total weight of the electrode material.
[0065] When the electrode for a lithium ion secondary battery is a positive electrode, the positive electrode active material may be used without particular limitation as long as it is a material capable of reversibly intercalating / deintercalating lithium ions.
[0066] In one example, the positive electrode active material may be a composite oxide or phosphate including cobalt, manganese, nickel, iron, or a combination of lithium and these metals.
[0067] In another example, the positive electrode active material may be a compound represented by any one of the following chemical formulas: Li a A 1-b R b D2(0.90≤a≤1.8, 0≤b≤0.5); Li a E 1-b R b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); LiE 2-b R b O 4-c D c (0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b R c D d (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d≤2);Li a Ni 1-b-c Co b R c O 2-d Zd (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d<2);Li a Ni 1-b-c Co b R c O 2-d Z2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d<2);Li a Ni 1-b- c Mr b R c D d (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d≤2);Li a Ni 1-b-c Mr b R c O 2-d Z d (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d<2);Li a Ni 1-b-c Mr b R c O 2-d Z2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d<2);Li a Ni b HAVE BEEN c G d O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0.001≤d≤0.1);Li a Ni b Co c Mr d G e O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0≤d≤0.5,0.001≤e≤0.1);Li a NiG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a CoG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a MnG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn2G bO4(0.90≤a≤1.8, 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiTO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2); and LiFePO4.
[0068] In the above chemical formula, A is Ni, Co, Mn or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; Z is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; T is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.
[0069] Those having a coating on the surface of the positive electrode active material can be used, or a mixture of the positive electrode active material and the positive electrode active material having a coating can be used. As the coating element contained in the coating, Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or a mixture thereof can be used.
[0070] According to one embodiment, based on the gross weight of the electrode material composition, the electrode active material may be included in an amount of 80 wt % to 95 wt %. Preferably, based on the gross weight of the electrode material composition, the content of the positive electrode active material may be 82 wt % to 95 wt %, or 82 wt % to 93 wt %, or 85 wt % to 93 wt %, or 85 wt % to 90 wt %.
[0071] When the electrode for a lithium ion secondary battery is a negative electrode, the negative electrode active material may include a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, a lithium metal alloy, a material capable of doping and dedoping lithium, and a transition metal oxide.
[0072] As a material capable of reversibly embedding and de-embedding lithium ions, crystalline carbon, amorphous carbon, or a mixture thereof as a carbonaceous material can be exemplified. Specifically, the carbonaceous material can be natural graphite, artificial graphite, crystalline graphite (Kishgraphite), pyrolytic carbon, mesophase pitch, carbon fiber based on mesophase pitch, mesophase carbon microspheres, coke derived from petroleum or coal tar pitch, soft carbon, hard carbon, etc.
[0073] The lithium metal alloy may include an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, Sn, Bi, Ga, and Cd.
[0074] Materials capable of doping and de-doping lithium may include Si, Si-C composite materials, SiO x (where 0 < x < 2), Si-Q alloys (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, but not Si), Sn, SnO2, Sn-R (where R is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, but not Sn), etc. In addition, as materials capable of doping and de-doping lithium, at least one of the above examples may be mixed with SiO2 and then used. Q and R may be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, etc.
[0075] In addition, transition metal oxides may include vanadium oxides, lithium vanadium oxides, lithium titanium oxides, etc.
[0076] Preferably, the negative electrode active material may include one or more compounds selected from carbonaceous materials and silicon compounds. Here, as previously exemplified, the carbonaceous material is a material containing at least one of the following: natural graphite, artificial graphite, crystalline graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fiber, mesophase carbon microspheres, coke derived from petroleum or coal tar pitch, soft carbon, and hard carbon. In addition, the silicon compound may be the Si-containing compound exemplified previously, i.e., Si, Si-C composite materials, SiO x (where 0 < x < 2), Si-Q alloys, mixtures thereof, or mixtures of at least one of them with SiO2.
[0077] According to one embodiment, based on the total weight of the electrode material composition, the negative electrode active material may be included in an amount of 85 wt% to 98 wt%. Preferably, based on the total weight of the negative electrode material composition, the content of the negative electrode active material may be 85 wt% to 97 wt%, or 87 wt% to 97 wt%, or 87 wt% to 95 wt%, or 90 wt% to 95 wt%.
[0078] According to one embodiment, in order to achieve appropriate performance, the thickness of the electrode active material layer is preferably adjusted within the range of 5 μm to 500 μm, or 5 μm to 450 μm, or 10 μm to 450 μm.
[0079] Meanwhile, the electrode for a lithium ion secondary battery includes a porous layer laminated on an electrode current collector layer.
[0080] According to one embodiment, the porous layer includes a polymer binder and inorganic fine particles dispersed in the polymer binder.
[0081] In particular, the polymer binder includes a copolymer containing a hard segment of the following Chemical Formula 1 and a soft segment of the following Chemical Formula 2:
[0082] [Chemical formula 1]
[0083]
[0084] Wherein in Chemical Formula 1,
[0085] R 1 and R 3 Each independently Among them A 1 To A 3 are each independently hydrogen or an alkyl group having 1 to 3 carbon atoms, and L 1 is a chemical bond or a methylene group;
[0086] R 2 is an alkylene group having 1 to 5 carbon atoms;
[0087] [Chemical formula 2]
[0088]
[0089] Wherein in Chemical Formula 2,
[0090] R 4 It is an alkylene group having 3 to 6 carbon atoms.
[0091] The copolymer has a hard segment capable of hydrogen bonding with the electrode active material layer and a soft segment that gives the copolymer high flexibility. Therefore, the bonding between the porous layer and the electrode active material layer is tight, and the porous layer is also given high flexibility, thereby being able to exhibit excellent durability during charging and discharging.
[0092] In the copolymer, R 1 and R 3 Each independently
[0093] Among them, A 1 To A 3 are each independently hydrogen or an alkyl group having 1 to 3 carbon atoms, and L 1 is a chemical bond or a methylene group. Preferably, A 1 To A 3 L may be independently hydrogen, methyl, or ethyl. 1 It may be a methylene group.
[0094] According to one embodiment, R 1 and R 3 Each independently may have a structure derived from 4,4′-diphenylmethane diisocyanate (4,4′-MDI), 1,4-phenylene diisocyanate, 1,3-phenylene diisocyanate, 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), or 1,5-naphthalene diisocyanate.
[0095] According to one embodiment, R 1 and R 3 Can be independently
[0096] According to one embodiment, R 1 and R 3 may each have a derivative of 4,4'-diphenylmethane diisocyanate (4,4'-MDI). structure.
[0097] In the copolymer, R 2 is an alkylene group having 1 to 5 carbon atoms. According to one embodiment, R 2 It may have the above structure derived from methylenediamine, ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, or 1,5-diaminopentane. 2 It may be a methylene group (*-CH2-*), an ethylene group (*-CH2-CH2-*) or a propylene group (*-CH2-CH2-CH2-*). According to one embodiment, R 2 The group may have a structure of ethylene (*-CH2-CH2-*) derived from ethylenediamine (EDA).
[0098] In chemical formula 2, R 4 is an alkylene group having 3 to 6 carbon atoms. 4 It may be a propylene group (*-CH2-CH2-CH2-*) or a butylene group (*-CH2-CH2-CH2-CH2-*). According to one embodiment, R 4It may have a structure derived from polytrimethylene ether glycol or polytetramethylene ether glycol. According to one embodiment, R 4 It may have a structure of a butylene group (*-CH2-CH2-CH2-CH2-*) derived from polytetramethylene ether glycol (PTMEG).
[0099] As a non-limiting example, the copolymer may be a copolymer comprising a hard segment of Chemical Formula 1 and a soft segment of Chemical Formula 2, wherein R 1 and R 3 Each having a derivative of 4,4'-diphenylmethane diisocyanate (4,4'-MDI) The structure of R 2 It has a structure of ethylene (*-CH2-CH2-*) derived from ethylenediamine (EDA); in the soft segment of Chemical Formula 2, R 4 It has a structure of a butylene group (*-CH2-CH2-CH2-CH2-*) derived from polytetramethylene ether glycol (PTMEG).
[0100] According to one embodiment, the copolymer may include the hard segment and the soft segment in a molar ratio of 80:20 to 95:5.
[0101] In order to ensure the bonding properties with the electrode active material layer and to give the polymer binder containing the copolymer appropriate mechanical properties, the molar ratio between the hard segment and the soft segment is preferably 80:20 or more. In addition, in order to give the porous layer high flexibility, the molar ratio between the hard segment and the soft segment is preferably 95:5 or less.
[0102] Specifically, the molar ratio between the hard segment and the soft segment may be 80:20 or more, or 85:15 or more; and 95:5 or less, or 90:10 or less.
[0103] Preferably, the molar ratio between the hard segment and the soft segment may be 80:20 to 95:5, or 85:15 to 95:5, or 85:15 to 90:10.
[0104] According to one embodiment, the weight average molecular weight (Mw) of the copolymer is from 100,000 g / mol to 1,000,000 g / mol.
[0105] In order to achieve the improved effect due to the application of the copolymer, the weight average molecular weight (Mw) of the copolymer can be 100,000 g / mol or more, or 150,000 g / mol or more; and 1,000,000 g / mol or less, or 800,000 g / mol or less, or 600,000 g / mol or less, or 400,000 g / mol or less. Preferably, the weight average molecular weight (Mw) of the copolymer can be 100,000 g / mol to 1,000,000 g / mol; or 150,000 g / mol to 1,000,000 g / mol; or 150,000 g / mol to 800,000 g / mol; or 150,000 g / mol to 600,000 g / mol; or 150,000 g / mol to 400,000 g / mol.
[0106] As a non-limiting example, the weight average molecular weight (Mw) can be measured using an Agilent PL-GPC 220 equipped with a PolarGel MIXED-L column (Polymer Laboratories) with a length of 300 mm. The measuring temperature is 65 ° C, tetrahydrofuran or dimethylformamide is used as a solvent, and the flow rate is 1 mL / min. The sample is prepared at a concentration of 10 mg / 10 mL and then fed in an amount of 100 μL. Mw and Mn values are obtained with reference to a calibration curve formed using polystyrene standards. Eight polystyrene standard samples each having a molecular weight (g / mol) of 580 / 3,940 / 8,450 / 31,400 / 70,950 / 316,500 / 956,000 / 4,230,000 are used.
[0107] According to one embodiment, as the copolymer, a product prepared to satisfy the above-mentioned structure and weight average molecular weight, or a commercial product (eg, spandex, etc.) may be used.
[0108] In addition, the polymer binder may also include one or more compounds selected from the following: polyetherimide, polyvinylidene fluoride, poly(vinylidene fluoride-co-trichloroethylene), poly(vinylidene fluoride-co-trifluorochloroethylene), poly(vinylidene fluoride-co-trifluoroethylene), poly(vinylidene fluoride-co-tetrafluoroethylene), poly(vinylidene fluoride-co-hexafluoropropylene), butyl acrylate, polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber and polyimide.
[0109] According to one embodiment, in order to achieve an improved effect due to the use of the copolymer, the polymer binder is preferably included in an amount of 10 wt % or more, or 10 wt % to 100 wt %, or 30 wt % to 100 wt %, or 50 wt % to 100 wt %, based on the total weight of the polymer binder comprising the copolymer containing the hard segment of Chemical Formula 1 and the soft segment of Chemical Formula 2.
[0110] The inorganic fine particles form micropores due to the empty spaces between the particles, maintain their physical form at high temperatures, and are electrochemically stable.
[0111] It is preferred that the inorganic fine particles do not undergo oxidation and / or reduction reactions within the operating voltage range of the secondary battery (e.g., 0V to 5V based on Li / Li+). The inorganic fine particles preferably have a high electrolyte ion transport capacity. The inorganic fine particles preferably have a density as low as possible so that they can be well dispersed in the polymer binder. In addition, the inorganic fine particles preferably have a high dielectric constant so that they can contribute to improving the degree of dissociation of the electrolyte salt in the electrolyte.
[0112] Preferably, the inorganic fine particles may be one or more selected from inorganic particles having a dielectric constant of 1 or more, inorganic particles having piezoelectricity, and inorganic particles having a lithium ion transporting capability.
[0113] In one example, inorganic particles such as SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, boehmite (AlO(OH)), Al(OH)3, TiO2 and SiC have a dielectric constant of 1 or greater and can therefore be preferably used as inorganic fine particles.
[0114] In another example, inorganic particles with piezoelectricity are non-conductive under normal pressure but become conductive due to changes in their internal structure when a certain pressure is applied. The piezoelectric inorganic particles have a high dielectric constant characteristic with a dielectric constant of 100 or more. In addition, when the piezoelectric inorganic particles are stretched or compressed under the application of a certain range of pressure, they generate charges, causing one surface to be positively (+) charged and the other surface to be negatively (-) charged, thereby generating a potential difference between the two surfaces. Due to the above characteristics of the piezoelectric inorganic particles, when an internal short circuit occurs in the electrode of a secondary battery due to an external shock, direct contact between the positive electrode and the negative electrode can be prevented, and the voltage can be gradually reduced and the safety can be improved. As the piezoelectric inorganic particles, inorganic particles such as BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3 (PLZT), Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT) and HfO2 can be preferably applied.
[0115] In yet another example, inorganic particles with lithium ion transport ability refer to inorganic particles that contain lithium element but have the function of enabling lithium ions to move without storing lithium. Inorganic particles with lithium ion transport ability can improve the lithium ion conductivity in the battery. Examples of such inorganic particles include, for example, Li3PO4, Li x Ti y (PO4)3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO3 (0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4) and Li x P y S zInorganic particles where (0 < x < 3, 0 < y < 3, 0 < z < 7).
[0116] Preferably, the inorganic fine particles can be one or more selected from the following: SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, AlO(OH), Al(OH)3, TiO2, SiC, BaTiO3, Pb(Zr,Ti)O3, Pb 1- x La x Zr 1-y Ti y O3, Pb(Mg 1 / 3 Nb 2 / 3 )O3 - PbTiO3, HfO2, Li3PO4, Li x Ti y (PO4)3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO3 (0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4) and Li x P y S z (0 < x < 3, 0 < y < 3, 0 < z < 7).
[0117] The particle size of the inorganic fine particles is preferably from 0.001 μm to 10 μm. To ensure dispersibility in the porous layer, the particle size of the inorganic fine particles is preferably 0.001 μm or greater. However, if the particle size of the inorganic fine particles is too large, the thickness of the porous layer increases and the mechanical properties deteriorate, and the overly large pore size may cause an internal short circuit during charging and discharging of the secondary battery. Therefore, the particle size of the inorganic fine particles is preferably 10 μm or less.
[0118] According to one embodiment, the porous layer may include 0.5 wt % to 45 wt % of the polymer binder and 55 wt % to 99.5 wt % of the inorganic fine particles.
[0119] In order to give the porous layer appropriate porosity and insulating properties, the inorganic fine particles are preferably contained in an amount of 55 wt % or more, or 60 wt % or more, or 65 wt % or more, or 70 wt % or more, or 75 wt % or more, or 80 wt % or more. However, if the inorganic fine particles are contained in an excessive amount, the mechanical properties of the porous layer may be reduced due to the weakening of the adhesive force. Therefore, the inorganic fine particles are preferably contained in an amount of 99.5 wt % or less, or 99 wt % or less, or 95 wt % or less.
[0120] Specifically, the porous layer may contain 55 wt % to 99.5 wt %, or 60 wt % to 99.5 wt %, or 65 wt % to 99.5 wt %, or 70 wt % to 99.5 wt %, or 75 wt % to 99.5 wt %, or 80 wt % to 99.5 wt %, or 80 wt % to 99 wt %, or 80 wt % to 95 wt % of inorganic fine particles, and the remainder of a polymer binder.
[0121] According to one embodiment, the porosity of the porous layer may be 40% to 80%.
[0122] In terms of ensuring lithium ion permeability, the porosity of the porous layer is preferably 40% or more, or 45% or more, or 50% or more. However, if the porosity of the porous layer is too large, it may be difficult to ensure the adhesion between the porous layer and the electrode, and an internal short circuit may occur during the charging and discharging of the lithium ion secondary battery. Therefore, the porosity of the porous layer is preferably 80% or less, or 75% or less, or 70% or less.
[0123] Specifically, the porosity of the porous layer may be 40% to 80%, or 45% to 80%, or 45% to 75%, or 50% to 75%, or 50% to 70%.
[0124] The porosity can be measured by preparing a slurry for forming a porous layer and then coating the slurry onto a release film to produce an independent porous layer. That is, the composition and process conditions that can ensure the porosity within the above range can be established by experimental methods, and these can be applied to actual production.
[0125] Porosity can be measured using scanning electron microscopy images (SEM), or can be measured using an adsorbed gas such as nitrogen and a BET device, or can be measured by methods such as mercury intrusion porosimetry or capillary flow porosimetry. Alternatively, porosity can be calculated from the thickness, weight, and theoretical density of the resulting porous layer.
[0126] The porous layer preferably has a porosity within a range suitable for exhibiting the characteristics of the porous layer. If the porosity of the porous layer is too large, an internal short circuit may occur during charging and discharging of the lithium ion secondary battery. Therefore, the porosity of the porous layer is preferably 60% or less.
[0127] According to one embodiment, the thickness of the porous layer is preferably adjusted within the range of 5 μm to 100 μm, or 5 μm to 50 μm, or 10 μm to 50 μm, to achieve appropriate performance.
[0128] Meanwhile, in the entire region between the electrode active material layer and the porous layer, there may be an interface layer in which the electrode material composition contained in the electrode active material layer and the porous composition contained in the porous layer are mixed.
[0129] In one example, the interface layer is a layer consisting of greater than 0 wt % and less than 100 wt % of the electrode material composition and less than 100 wt % and greater than 0 wt % of the porous composition.
[0130] According to another embodiment of the present disclosure, there is provided a method for manufacturing an electrode for a lithium ion secondary battery, the method comprising the following steps:
[0131] forming an electrode active material layer by applying an electrode material composition including an electrode active material to an electrode current collector layer;
[0132] preparing an inorganic fine particle dispersion in which inorganic fine particles and a dispersant are dispersed in a solvent;
[0133] preparing a binder solution comprising a polymer binder comprising a copolymer including a hard segment of Chemical Formula 1 and a soft segment of Chemical Formula 2 dissolved in a solvent;
[0134] preparing a slurry for forming a porous layer by mixing a binder solution with an inorganic fine particle dispersion; and
[0135] The porous layer is formed by applying a slurry for forming a porous layer onto the electrode active material layer.
[0136] The above-mentioned electrode for lithium ion secondary battery can be provided by the above-mentioned production method.
[0137] First, a step of forming an electrode active material layer by applying an electrode material composition containing an electrode active material to an electrode current collector layer may be performed. In the above steps, the electrode current collector and the electrode material composition are replaced with the above contents, respectively. The electrode active material layer may be formed by applying the electrode material composition to the electrode current collector layer and drying it.
[0138] Separately from the above steps, there may be performed a step of preparing an inorganic fine particle dispersion in which inorganic fine particles and a dispersant are dispersed in a solvent; a step of preparing a binder solution in which a polymer binder is dissolved in a solvent; and a step of preparing a slurry for forming a porous layer by mixing the binder solution with the inorganic fine particle dispersion.
[0139] As a result of further research by the inventors, it was determined that when preparing a slurry for forming a porous layer, the agglomeration phenomenon of inorganic fine particles and the distribution state of the polymer binder and inorganic fine particles can vary according to the mixing order and mixing method of the constituent components. It was also determined that depending on the distribution state of the polymer binder and inorganic fine particles, it can have a significant influence on the bonding force of the porous layer and the electrode active material layer.
[0140] In one example, when a binder solution in which a polymer binder is dissolved in a solvent is prepared and then inorganic fine particles are added thereto to prepare a slurry for forming a porous layer, it becomes impossible to provide an electrode for a lithium ion secondary battery satisfying the above characteristics, for example, the dispersibility of the inorganic fine particles is significantly reduced.
[0141] According to one embodiment, since the manufacturing method of the present disclosure includes the following steps: preparing an inorganic fine particle dispersion; preparing a binder solution; and preparing a slurry for forming a porous layer by mixing the binder solution with the inorganic fine particle dispersion, an electrode for a lithium ion secondary battery can be provided in which the porous layer and the electrode active material layer are tightly combined and the porous layer is endowed with high flexibility.
[0142] In the above steps, the inorganic fine particles and the polymer binder are replaced with the above-mentioned ones, respectively.
[0143] As the dispersant, a compound known in the technical field to which the present disclosure pertains to dispersion of inorganic fine particles, such as a carboxylic acid-modified polyester copolymer and acetic acid, may be used.
[0144] In addition, non-aqueous organic solvents can be used as solvents. Specifically, non-aqueous organic solvents may include: ester-based solvents, such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether-based solvents, such as dibutyl ether and tetrahydrofuran; ketone-based solvents, such as cyclohexanone; aromatic hydrocarbon-based solvents, such as benzene and fluorobenzene; carbonate-based solvents, such as N-methyl-2-pyrrolidone (NMP), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol-based solvents, such as ethanol and isopropanol; nitrile, such as R-CN (wherein R is a C2 to C20 linear, branched or cyclic hydrocarbon group, which may contain a double bond aromatic ring or an ether bond); amide, such as dimethylformamide; dioxolane, such as 1,3-dioxolane; cyclopentane, etc. In the above examples, a carbonate-based solvent suitable for dispersing inorganic fine particles may be preferably used as the nonaqueous organic solvent.
[0145] According to one embodiment, the slurry for forming the porous layer preferably has a solid content including inorganic fine particles of 30% by weight to 95% by weight.
[0146] If the solid content of the porous slurry is too high, it may cause an increase in viscosity and may not easily penetrate into the pore area of the electrode active material layer, thereby failing to form an interface layer 25 having a proper structure. However, if the solid content of the porous slurry is too low, a pinhole phenomenon may occur when applied to the electrode active material layer.
[0147] Specifically, the solid content of the porous slurry may be 30 wt % or more, or 35 wt % or more; and 95 wt % or less, or 90 wt % or less. Preferably, the solid content of the porous slurry may be 30 wt % to 95 wt %, or 30 wt % to 90 wt %, or 35 wt % to 90 wt %.
[0148] Next, a step of forming a porous layer by applying a slurry for forming a porous layer to the electrode active material layer is performed. The porous layer can be formed by applying a slurry for forming a porous layer to the electrode active material layer and drying it. The above steps can be performed in consideration of the thickness of the above-mentioned electrode active material layer and the porous layer.
[0149] In the above steps, drying is preferably performed at a temperature of 50° C. to 150° C., or 60° C. to 150° C., or 60° C. to 120° C., or 65° C. to 110° C., respectively. If the drying temperature does not satisfy the above range, drying efficiency may decrease or the shape of each layer may change, which may cause defects.
[0150] According to another exemplary embodiment of the present disclosure, there is provided a slurry for forming a porous layer of an electrode for a lithium ion secondary battery, the slurry including: a polymer binder and inorganic fine particles dispersed in the polymer binder.
[0151] In the slurry for forming the porous layer, the polymer binder and the inorganic fine particles are replaced with the above-mentioned ones, respectively.
[0152] The slurry for forming the porous layer can be obtained by: a step of preparing an inorganic fine particle dispersion in which inorganic fine particles and a dispersant are dispersed in a solvent; a step of preparing a binder solution in which a polymer binder containing a copolymer containing a hard segment of Chemical Formula 1 and a soft segment of Chemical Formula 2 is dissolved in the solvent; and a step of preparing the slurry for forming the porous layer by mixing the binder solution with the inorganic fine particle dispersion.
[0153] According to still another exemplary embodiment of the present disclosure, there is provided a lithium ion secondary battery including the above-mentioned electrode.
[0154] In one example, a lithium ion secondary battery may include an electrode assembly including a counter electrode disposed on a porous layer of the electrode; an electrolyte impregnated in the electrode assembly; and a battery case sealing and storing the electrode assembly and the electrolyte.
[0155] Since the lithium ion secondary battery includes the above-described electrode assembly, it may exhibit excellent durability and stable performance.
[0156] The lithium ion secondary battery may have various shapes, such as a prismatic shape, a cylindrical shape, or a pouch shape.
[0157] Lithium ion secondary batteries can be used as energy sources with improved performance and safety in the fields of portable electronic devices such as mobile phones, notebook computers, tablet computers, mobile batteries, and digital cameras; and in the fields of transportation vehicles such as electric vehicles, electric motorcycles, and personal mobility devices.
[0158] According to one embodiment, the electrolyte can be used without particular limitation, as long as it is known to be suitable for lithium ion secondary batteries in the technical field to which the present invention belongs. For example, the electrolyte can be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc.
[0159] Specifically, the electrolyte may include a non-aqueous organic solvent and a lithium salt.
[0160] The nonaqueous organic solvent may be used without particular limitation as long as it can function as a medium through which ions participating in the electrochemical reaction of the battery can move.
[0161] Specifically, the non-aqueous organic solvents include: ester-based solvents, such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether-based solvents, such as dibutyl ether and tetrahydrofuran; ketone-based solvents, such as cyclohexanone; aromatic hydrocarbon-based solvents, such as benzene and fluorobenzene; carbonate-based solvents, such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol-based solvents, such as ethanol and isopropanol; nitriles, such as R-CN (wherein R is a C2 to C20 linear, branched or cyclic hydrocarbon group, which may contain a double bond aromatic ring or an ether bond); amides, such as dimethylformamide; dioxolanes, such as 1,3-dioxolane; cyclopentane sulfone, etc.
[0162] In the above examples, a carbonate-based solvent may be preferably used as the non-aqueous organic solvent.
[0163] In particular, considering the charging and discharging performance of the battery and the compatibility with the sacrificial positive electrode material, the non-aqueous organic solvent may preferably be a mixture of a cyclic carbonate (e.g., ethylene carbonate and propylene carbonate) having high ionic conductivity and high dielectric constant and a linear carbonate (e.g., ethyl methyl carbonate, dimethyl carbonate and diethyl carbonate) having a low viscosity carbonate. In this case, mixing and using cyclic carbonate and linear carbonate in a volume ratio of 1:1 to 1:9 may be beneficial to achieving the above-mentioned properties.
[0164] In addition, as the non-aqueous organic solvent, a solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:2 to 1:10; or a solvent in which ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 1 to 3:1 to 9:1 can be preferably used.
[0165] The lithium salt contained in the electrolyte is dissolved in the non-aqueous organic solvent and serves as a lithium ion source in the battery, which enables the basic operation of the lithium ion secondary battery and facilitates the movement of lithium ions between the positive electrode and the negative electrode.
[0166] The lithium salt may include LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiFSI, LiTFSI, LiCl, LiI and LiB(C2O4)2, etc. Specifically, the lithium salt may be LiPF6, LiFSI, LiTFSI, and mixtures thereof.
[0167] The lithium salt may be included in the electrolyte at a concentration of 0.1 M to 2.0 M. The lithium salt included in the concentration range imparts appropriate conductivity and viscosity to the electrolyte, thereby exhibiting excellent electrolyte performance.
[0168] Optionally, the electrolyte may contain additives for the purpose of improving battery life characteristics, suppressing decrease in capacity in the battery, improving battery discharge capacity, and the like.
[0169] For example, the additive may include a halogenated alkylene carbonate-based compound such as difluoroethylene carbonate; or pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. The additive may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.
[0170] Beneficial Effects
[0171] According to the present disclosure, provided are an electrode for a lithium ion secondary battery, a method for manufacturing the same, and a lithium ion secondary battery including the electrode, wherein the electrode for a lithium ion secondary battery has a close bond between a porous layer and an electrode active material layer and also imparts high flexibility to the porous layer, thereby being able to exhibit excellent durability during charge and discharge. BRIEF DESCRIPTION OF THE DRAWINGS
[0172] Figure 1 is a scanning electron microscope (SEM) image of the electrode for a lithium ion secondary battery according to Example 1.
[0173] Figure 2 This is a SEM image of the electrode for a lithium ion secondary battery according to Example 2.
[0174] Figure 3 This is a SEM image of the electrode for a lithium ion secondary battery according to Example 3.
[0175] Figure 4 This is a SEM image of the electrode for a lithium ion secondary battery according to Example 4.
[0176] Figure 5 This is a SEM image of the electrode for a lithium ion secondary battery according to Example 5.
[0177] Figure 6 This is a SEM image of the lithium ion secondary battery electrode according to Comparative Example 1.
[0178] Figure 7This is a SEM image of the lithium ion secondary battery electrode according to Comparative Example 1. DETAILED DESCRIPTION
[0179] Hereinafter, the action and effect of the present invention will be described in more detail with reference to specific embodiments of the present invention. However, it is presented as an example to help understand the present invention. The following examples are not intended to limit the scope of the present invention in any way. It will be apparent to those skilled in the art that various changes and modifications can be made within the scope of the present invention and the technical spirit.
[0180] Example 1
[0181] An electrode material composition was prepared, the electrode material composition consisting of: 95.6 wt % of an active material, the active material consisting of 90 wt % of a graphite active material in which artificial graphite and natural graphite were mixed at a ratio of 3:7 and 10 wt % of SiO; 1 wt % of acetylene black as a conductive material; 1.1 wt % of carboxymethyl cellulose (CMC) and 2.3 wt % of styrene-butadiene rubber (SBR) as a binder. The electrode material composition was coated on one surface of a copper current collector having a thickness of 8 μm using a comma coater. It was dried at 130° C. and rolled to prepare a negative electrode plate having a negative electrode active material layer laminated thereon. The negative electrode active material layer was formed to have a porosity of 24% and a thickness of 44 μm.
[0182] Inorganic fine particles AlO (OH) and a dispersant (BYK, DISPERBYK-111) were mixed with N-methyl-2-pyrrolidone (NMP) to prepare an inorganic fine particle dispersion having a solid content of 40%. At this time, the particle size (D60) of the inorganic fine particles measured using a particle size analyzer was analyzed to be 400 nm.
[0183] As a polymer binder, spandex (weight average molecular weight: 200,000 g / mol) and poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP) were mixed at a weight ratio of 50:50 to prepare a 10 wt % binder solution dissolved in NMP.
[0184] Here, spandex is a block copolymer composed of a hard segment of Chemical Formula 1 and a soft segment of Chemical Formula 2. Spandex is a copolymer including a hard segment of Chemical Formula 1 and a soft segment of Chemical Formula 2, wherein R 1 and R 3 Each having a derivative of 4,4'-diphenylmethane diisocyanate (4,4'-MDI) The structure of R 2 It has a structure of ethylene (*-CH2-CH2-*) derived from ethylenediamine (EDA); in the soft segment of Chemical Formula 2, R4 It has a structure of butylene (*-CH2-CH2-CH2-CH2-*) derived from polytetramethylene ether glycol (PTMEG). The molar ratio of hard segment to soft segment in spandex is 85:15.
[0185] A slurry for forming a porous layer in which the inorganic fine particle dispersion and the binder solution are uniformly mixed using a homogenizer mixer is obtained.
[0186] The slurry for forming the porous layer was applied on the negative electrode active material layer and then dried at 130° C. to obtain a negative electrode plate having a porous layer formed on the negative electrode active material layer. The composition of the porous layer consisted of 90 wt % of inorganic fine particles and 10 wt % of a polymer binder. The porous layer was formed to have a thickness of 20 μm.
[0187] The negative electrode plate was punched into a size of 31 mm×43 mm using a die punch machine to prepare a negative electrode portion.
[0188] A mixture of 94 wt% of LiNiCoMnO2 (Ni:Co:Mn=8:1:1) as a positive electrode active material, 3 wt% of conductive carbon black (Super P; IMERYS Graphite & Carbon) as a conductive material, and 3 wt% of polyvinylidene fluoride as a binder was added to NMP to prepare a uniformly dispersed slurry. The slurry was applied to one surface of an aluminum current collector, which was then dried and rolled to prepare a positive plate having a positive electrode active material layer laminated thereon. The positive plate was punched using a die punch to prepare a 30×42 mm positive electrode portion.
[0189] The positive electrode active material layer of the positive electrode portion is provided in contact with the porous layer of the negative electrode portion to produce an electrode assembly.
[0190] The electrode assembly was housed in a pouch to form a small battery, and an electrolyte was injected into the pouch to manufacture five lithium secondary batteries.
[0191] At this time, as an electrolyte solution, a solution in which 1.0 M LiPF6 and 2 wt% of vinylene carbonate (VC) were dissolved in a nonaqueous organic solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 3:7 was used.
[0192] Example 2
[0193] A negative electrode portion, a positive electrode portion, and a lithium ion secondary battery were produced in the same manner as in Example 1, except that only spandex was used as the polymer binder instead of a mixture of spandex and PVdF-HFP.
[0194] Example 3
[0195] A negative electrode portion, a positive electrode portion and a lithium ion secondary battery were produced in the same manner as in Example 1, except that the composition of the slurry for forming the porous layer was adjusted so that the porous layer consisted of 92 wt % of inorganic fine particles and 8 wt % of the polymer binder.
[0196] Example 4
[0197] A negative electrode portion, a positive electrode portion, and a lithium ion secondary battery were produced in the same manner as in Example 3, except that only spandex was used as the polymer binder instead of a mixture of spandex and PVdF-HFP.
[0198] Example 5
[0199] A negative electrode portion, a positive electrode portion and a lithium ion secondary battery were produced in the same manner as in Example 1, except that the composition of the slurry for forming the porous layer was adjusted so that the porous layer consisted of 85 wt % of inorganic fine particles and 15 wt % of a polymer binder.
[0200] Comparative Example 1
[0201] A negative electrode portion, a positive electrode portion, and a lithium ion secondary battery were produced in the same manner as in Example 1, except that a mixture of polyetherimide and PVdF-HFP in a weight ratio of 50:50 was used as the polymer binder instead of a mixture of spandex and PVdF-HFP.
[0202] Comparative Example 2
[0203] A negative electrode portion, a positive electrode portion, and a lithium ion secondary battery were produced in the same manner as in Example 1, except that only PVdF-HFP was used as the polymer binder instead of a mixture of spandex and PVdF-HFP.
[0204] Experimental Example 1
[0205] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the copolymers prepared in Preparation Examples were measured using gel permeation chromatography (GPC, Waters E2640).
[0206] In detail, the copolymer is dissolved in hexafluoroisopropanol (HFIP) at a concentration of 2mg / ml, and 20μl of it is injected into GPC. HFIP is used as the mobile phase of GPC, and introduced at a flow rate of 1.0mL / minute, and analyzed at 40°C. Two Agilent Mixed-B columns are connected in series. As a detector, an RI detector is used. The Mw value is obtained using a calibration curve formed using a polystyrene standard sample. Nine polystyrene standard samples with weight-average molecular weights of 2,000g / mol, 10,000g / mol, 30,000g / mol, 70,000g / mol, 200,000g / mol, 700,000g / mol, 2,000,000g / mol, 4,000,000g / mol, or 10,000,000g / mol are used.
[0207] Experimental Example 2
[0208] The bending characteristics of the negative electrode plates according to the examples and comparative examples were evaluated using a mandrel method. The diameters of the bars where cracks occurred are shown in Table 1 below.
[0209] Experimental Example 3
[0210] The negative electrode plates in which the porous layers according to the examples and the comparative examples were formed on the negative electrode active material layers were observed with a scanning electron microscope, and the results are shown in FIG. Figure 1 (Example 1), Figure 2 (Example 2), Figure 3 (Example 3), Figure 4 (Example 4), Figure 5 (Example 5), and Figure 6 (Comparative Example 1) and Figure 7 (Comparative Example 2). Figure 1 , Figure 2 , Figure 6 and Figure 7 , (a) is a SEM image at a magnification of 1000 times, and (b) is a SEM image at a magnification of 5000 times. Figure 3 , Figure 4 and Figure 5 The SEM images were taken at a magnification of 5000 times.
[0211] Reference Figures 1 to 5 , a uniform surface condition without microcracks can be observed in the negative electrode plate according to the embodiment.
[0212] Reference Figure 6Due to the characteristics of the non-flexible polymer binder, cracks were easily observed in the negative electrode plate according to Comparative Example 1. Specifically, in Comparative Example 1, it was observed that the surface was rougher than that in Example 1, and relatively large pores of about 1 μm were unevenly distributed.
[0213] Reference Figure 7 , in the negative electrode plate according to Comparative Example 2, the surface roughness was slightly reduced compared to Comparative Example 1, but cracks on the surface could still be easily observed.
[0214] Experimental Example 4
[0215] Immediately after the lithium secondary batteries obtained in Examples and Comparative Examples (5 samples each) were produced, the open circuit voltage (OCV) was measured respectively and is shown in Table 1 below as an average value of the 5 samples.
[0216] The lithium secondary batteries obtained in Examples and Comparative Examples (5 samples each) were charged at 25° C. in CC-CV mode at 0.1 C (reference capacity: 4.5 mAh / cm 2 ) was charged until the voltage reached 4.2 V, and the voltage was maintained in CV mode until it reached 0.05 C. Subsequently, the formation process was performed by discharging to 2.5 V at 0.1 C, and the discharge capacity (mAh) is shown in the following Table 1 as an average value of five samples.
[0217] During the formation process, the number of defective samples in which charging and discharging did not normally occur due to short circuit among the five samples produced in the examples and comparative examples was determined and shown in Table 1 below.
[0218] [Table 1]
[0219]
[0220] Referring to the results of the experimental examples, the lithium secondary batteries of the examples exhibited excellent assembly stability, had no defects due to short circuits between the negative electrode portion and the positive electrode portion, and exhibited high discharge capacity.
[0221] The lithium ion secondary battery of Comparative Example 1 had a low initial open circuit voltage and a defect rate of about 60%, resulting in low assembly stability caused by low bending characteristics and surface cracks of the negative electrode plate.
[0222] In addition, the lithium ion secondary battery of Comparative Example 2 is slightly better than Comparative Example 1 in terms of bending characteristics and surface cracks of the negative electrode plate, but the initial open circuit voltage is still lower than that of the embodiment, and the defect rate is about 40%, indicating low assembly stability.
[0223] While the present disclosure has been particularly shown and described with reference to several embodiments and illustrative drawings, the disclosure is not limited to these embodiments, and it will be apparent to those skilled in the art that numerous modifications and variations are possible without departing from the spirit and scope of the invention as defined by the appended claims.
Claims
1. An electrode for a lithium-ion secondary battery, comprising: The electrode active material layer and the porous layer are laminated on the electrode current collector layer, The porous layer comprises a polymer binder and inorganic fine particles dispersed in the polymer binder, and the polymer binder comprises a copolymer comprising a hard segment of the following Chemical Formula 1 and a soft segment of the following Chemical Formula 2: [Chemical formula 1] Wherein in Chemical Formula 1, R 1 and R 3 Each independently Among them A 1 To A 3 are each independently hydrogen or an alkyl group having 1 to 3 carbon atoms, and L 1 is a chemical bond or a methylene group; R 2 is an alkylene group having 1 to 5 carbon atoms; [Chemical formula 2] Wherein in Chemical Formula 2, R 4 It is an alkylene group having 3 to 6 carbon atoms.
2. The lithium ion secondary battery electrode according to claim 1, wherein the R 1 and the R 3 Each independently 3 . The electrode for a lithium ion secondary battery according to claim 1 , wherein the copolymer comprises the hard segment and the soft segment in a molar ratio of 80:20 to 95:
5. 4 . The electrode for a lithium ion secondary battery according to claim 1 , wherein a weight average molecular weight (Mw) of the copolymer is 100,000 g / mol to 1,000,000 g / mol.
5. The electrode for a lithium ion secondary battery according to claim 1, wherein the polymer binder further comprises one or more compounds selected from the group consisting of polyetherimide, polyvinylidene fluoride, poly(vinylidene fluoride-co-trichloroethylene), poly(vinylidene fluoride-co-chlorotrifluoroethylene), poly(vinylidene fluoride-co-trifluoroethylene), poly(vinylidene fluoride-co-tetrafluoroethylene), poly(vinylidene fluoride-co-hexafluoropropylene), butyl acrylate, polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide. 6 . The electrode for a lithium ion secondary battery according to claim 5 , wherein the polymer binder is included in an amount of 10 wt % or more based on the total weight of the polymer binder including the copolymer containing the hard segment of Chemical Formula 1 and the soft segment of Chemical Formula 2.
7. The electrode for a lithium ion secondary battery according to claim 1, wherein the inorganic fine particles are one or more selected from the following: SrTiO3; SnO2; CeO2; MgO; NiO; CaO; ZnO; ZrO2; Y2O3; Al2O3; AlO(OH); Al(OH)3; TiO2; SiC; BaTiO3; Pb(Zr,Ti)O3; Pb 1-x La x Zr 1-y Ti y O3; Pb(Mg 1 / 3 Nb 2 / 3 )O3 - PbTiO3; HfO2; Li3PO4; Li x Ti y (PO4)3(0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3(0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO3(0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4) and Li x P y S z (0 < x < 3, 0 < y < 3, 0 < z < 7). 8 . The electrode for a lithium ion secondary battery according to claim 1 , wherein the inorganic fine particles have a particle size of 0.001 μm to 10 μm. 9 . The electrode for a lithium ion secondary battery according to claim 1 , wherein the porous layer contains 0.5 to 45 wt % of the polymer binder and 55 to 99.5 wt % of the inorganic fine particles.
10. A method for manufacturing the electrode for a lithium ion secondary battery according to claim 1, the method comprising the following steps: forming an electrode active material layer by applying an electrode material composition including an electrode active material to an electrode current collector layer; preparing an inorganic fine particle dispersion in which inorganic fine particles and a dispersant are dispersed in a solvent; preparing a binder solution in which a polymer binder including a copolymer including a hard segment of the following Chemical Formula 1 and a soft segment of the following Chemical Formula 2 is dissolved in a solvent; preparing a slurry for forming a porous layer by mixing the binder solution with the inorganic fine particle dispersion; as well as forming a porous layer by applying the slurry for forming a porous layer onto the electrode active material layer, [Chemical formula 1] Wherein in Chemical Formula 1, R 1 and R 3 Each independently Among them A 1 To A 3 are each independently hydrogen or an alkyl group having 1 to 3 carbon atoms, and L 1 is a chemical bond or a methylene group; R 2 is an alkylene group having 1 to 5 carbon atoms; [Chemical formula 2] Wherein in Chemical Formula 2, R 4 It is an alkylene group having 3 to 6 carbon atoms. 11 . The production method according to claim 10 , wherein the slurry for forming a porous layer has a solid content including the inorganic fine particles of 55 wt % to 99.5 wt %.
12. A slurry for forming a porous layer of an electrode for a lithium ion secondary battery, comprising: a polymer binder and inorganic fine particles dispersed in the polymer binder, wherein the polymer binder comprises a copolymer containing a hard segment of the following chemical formula 1 and a soft segment of the following chemical formula 2: [Chemical formula 1] Wherein in Chemical Formula 1, R 1 and R 3 Each independently Among them A 1 To A 3 are each independently hydrogen or an alkyl group having 1 to 3 carbon atoms, and L 1 is a chemical bond or a methylene group; R 2 is an alkylene group having 1 to 5 carbon atoms; [Chemical formula 2] Wherein in Chemical Formula 2, R 4 It is an alkylene group having 3 to 6 carbon atoms. 13 . The slurry for forming a porous layer for an electrode for a lithium ion secondary battery according to claim 12 , wherein the copolymer comprises the hard segment and the soft segment in a molar ratio of 80:20 to 95:
5. 14 . The slurry for forming a porous layer of an electrode for a lithium ion secondary battery according to claim 12 , wherein the polymer binder and the inorganic fine particles are contained in a ratio of 0.5 to 45 wt %:55 to 99.5 wt %. 15 . A lithium ion secondary battery comprising the lithium ion secondary battery electrode according to claim 1 .
